Cu assisted stabilization and nucleation of L12 precipitates in Al0.3CuFeCrNi2 fcc-based high entropy alloy. (1st May 2017) - Gwalani, B.; Choudhuri, D.; Soni, V.; Ren, Y.; Styles, M.; Hwang, J.Y.; Nam, S.J.; Ryu, H.; Hong, S.H.; Banerjee, R.
Abstract: A detailed investigation of precipitation of the ordered L12 (γ′) phase in a Al0.3 CrCuFeNi2 high entropy alloy (HEA), more generally referred to as a complex concentrated alloy (CCA), reveals the role of copper (Cu) on stabilization and precipitation of the ordered L12 (γ′) phase. Detailed characterization via coupling of scanning and transmission electron microscopy, and atom probe tomography revealed novel insights into Cu clustering within the face-centered cubic matrix of this HEA, leading to heterogeneous nucleation sites for the γ′ precipitates. The subsequent partitioning of Cu into the γ′ precipitates indicates their stabilization is due to Cu addition. The γ′ order-disorder transition temperature was determined to be ∼930 °C in this alloy, based on synchrotron diffraction experiments, involving in situ annealing. The growth and high temperature stability of the γ′ precipitates was also confirmed via systematic scanning electron microscopy investigations of samples annealed at temperatures in the range of 700–900 °C. The role of Cu revealed by this study can be employed in the design of precipitation strengthened HEAs, as well as in a more general sense applied to other types of superalloys, with the objective of potentially enhancing their mechanical properties at room and elevated temperatures. Graphical abstract: Image